DETERMINATION OF THE TOTAL POLYPHENOL AND ALKALOID CONTENT AND ANTIOXIDANT ACTIVITIES OF SOME PLANTS IN TRA VINH PROVINCE - relv; Ngoc Tram Nguyen Thi; Huynh Thi Hong Hoa; Mai Thi Thuy Lam (HUIT Journal of Science, 2025)
This study aimed to determine the total polyphenol and alkaloid contents, as well as the antioxidant activity of ethanolic extracts from five plant species collected in Tra Vinh province. The total polyphenol content (TPC) was measured using the Folin-Ciocalteu colorimetric method, and the total alkaloid content (TAC) was determined using UV-vis spectroscopy. Antioxidant activity was assessed via the DPPH radical scavenging assay. Results showed that TPC ranged from 91.60 to 512.67 mg GAE/g extract and TAC from 0.36 to 3.68 mg CE/g. The aerial part of Galphimia gracilis exhibited the strongest antioxidant activity (IC50 = 69.88 ± 0.63 μg/mL). A positive correlation was observed between polyphenol content and antioxidant activity, suggesting that polyphenol compounds significantly contribute to radical scavenging capacity. This is the first report on these species from Tra Vinh province, providing valuable data for future ethnobotanical and phytochemical studies.